Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Penurunan Nyeri Pada Pasien Post Operasi Sedang Di Rumah Sakit Umum Daerah Tanjungpinang - Multazam Multazam; Umi Eliawati; Sri Muharni (STIKes Ibnu Sina Ajibarang, 2023)
Surgery is a treatment procedure that involves opening the part of the body to be treated through an incision and ending with the closure of the stitches in the incision wound. Undergoing surgery is a difficult experience for patients. As a result of the surgical procedure, the patient will experience discomfort and pain. This research was conducted to determine the effect of deep breathing relaxation techniques on reducing pain in moderate post-operative patients at the Tanjungpinang Regional General Hospital in 2023. The research method was Pre-Experimental Design, with a pre-test and post-test approach without control. The sample consisted of 40 respondents in moderate post-operative patients at Tanjungpinang District Hospital using the Accidental Sampling technique. Data were processed using the Wilcoxon test. Univariate analysis before using the deep breathing relaxation technique with moderate levels of pain was 40 respondents (100%). Bivariate results show that there is an effect of deep breathing relaxation techniques on reducing pain in moderate post-operative patients with a p value of 0.000 (0.05). It was concluded that there was an effect of deep breathing relaxation techniques on reducing pain in moderate post-operative patients. It is hoped that moderate post-operative patients can apply deep breathing relaxation techniques to reduce pain intensity.